A Likelihood Framework for Modeling Pairwise Beta Diversity Patterns Based on the Tradeoff Between Colonization and Extinction - Wu, Yongbin; Chen, Youhua; Shen, Tsung-Jen (Frontiers in Ecology and Evolution, 2020)
Ecological communities are assembled by various mechanisms, including a tradeoff between colonization and extinction processes. However, it is still unclear how this tradeoff influences pairwise beta diversity pattern. Herein, we propose a novel likelihood framework to disentangle the compound impacts of species’ colonization and extinction rates on community-level compositional dissimilarity which are ignored by traditional indices. The framework infers two parameters of colonization and extinction rates, allowing ecologists to study their latitudinal or broad-scale spatial variation patterns and test the relative influences of associated environmental factors. More importantly, the likelihood-based model showed that multi-site beta diversity is essentially identical to the local colonization failure or extinction rate of species in newly colonized sites, but is not related to species’ colonization rates. Profoundly, the present likelihood model allows ecologists to explicitly infer the independent species’ colonization rate parameter and test its underpinning mechanisms, as it can be proven that this parameter would be only implicitly measured if used to compute multi-site beta diversity indices. KEYWORDS: beta diversity, island biogeography theory, ecological mechanisms, community assembly, biodiversity survey